Investigation of the photocatalytic transformation of acesulfame K in the presence of different TiO2-based materials. (February 2018) - López-Muňoz, M.J.; Daniele, A.; Zorzi, M.; Medana, C.; Calza, P.
Abstract: The photocatalytic transformation of acesulfame K – an artificial sweetener that has gained popularity over the last decades for being a calorie-free additive in food, beverages and several pharmaceutical products – was studied using three different photocatalysts, the benchmark TiO2 -P25 and two other forms of synthetized titanium oxides named TiO2 -SG1 and TiO2 -SG2. The two latter materials were synthesized by a sol gel process in which the hydrolysis rate of titanium n -butoxide was controlled by the water formed in situ through an esterification reaction between ethanol and acetic acid. The investigation included monitoring the sweetener disappearance, identifying its intermediate compounds, assessing mineralization and evaluating toxicity. The analyses were carried out using high-performance liquid chromatography (HPLC) coupled with a LTQ-Orbitrap analyzer via an electrospray ionization (ESI) in the negative ion mode. This is a powerful tool for the identification, characterization and measurement of the transformation products (TPs); overall 13 species were identified. The use of several semiconductors has pointed out differences in terms of both photocatalytic efficiency and mechanism: the assessment of the evolution kinetics of each species (TPs, total organic carbon and inorganic ions) has brought to the elaboration of a general transformation pathway of acesulfame K. TiO2 -SG2 proved to be the most efficient material in degrading the artificial sweetener and leads to the complete mineralization within 6 h of irradiation, while up to 16 h are required for TiO2 -P25. Graphical abstract: Image 1 Highlights: Acesulfame K was studied using different photocatalysts prepared via sol gel process. Differences in terms of both photocatalytic efficiency and mechanism occurred. The elaboration of a general transformation mechanism of acesulfame K was performed. TiO2 -Sol gel proved to be the most efficient material in degrading the sweetener.